2013
DOI: 10.1136/amiajnl-2012-001558
|View full text |Cite
|
Sign up to set email alerts
|

Use of the International Classification of Diseases, 9th revision, coding in identifying chronic hepatitis B virus infection in health system data: implications for national surveillance

Abstract: As the USA increases the use of EHR, surveillance using ICD-9 codes may be reliable to determine the burden of chronic HBV infection and would be useful to improve reporting by state and local health departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…The PPV of HBV infection-specific ICD-10-CM codes in this study was 45%, similar to the PPV of ICD-9-CM codes in the Michael E. DeBakey Veterans Affairs Medical Center (MDVAMC) study (43%) and lower than that in the University of Pennsylvania Health System (UPHS) (81%) and the Centers for Disease Control and Prevention Chronic Hepatitis Cohort Study (CHeCS), including the data from four large health-care systems (61%). [15][16][17] The sensitivity and specificity for HBV infection-specific codes were 46% and 83%, respectively, lower than in CHeCS (i.e., 84% and 99%, respectively). 17 The PPV of HCV infection-specific ICD-10-CM codes was 81%, which was lower than that in the MDVAMC study (93%), UPHS (89%), and CHeCS (92%).…”
Section: Comparison With Previous Studiesmentioning
confidence: 85%
See 2 more Smart Citations
“…The PPV of HBV infection-specific ICD-10-CM codes in this study was 45%, similar to the PPV of ICD-9-CM codes in the Michael E. DeBakey Veterans Affairs Medical Center (MDVAMC) study (43%) and lower than that in the University of Pennsylvania Health System (UPHS) (81%) and the Centers for Disease Control and Prevention Chronic Hepatitis Cohort Study (CHeCS), including the data from four large health-care systems (61%). [15][16][17] The sensitivity and specificity for HBV infection-specific codes were 46% and 83%, respectively, lower than in CHeCS (i.e., 84% and 99%, respectively). 17 The PPV of HCV infection-specific ICD-10-CM codes was 81%, which was lower than that in the MDVAMC study (93%), UPHS (89%), and CHeCS (92%).…”
Section: Comparison With Previous Studiesmentioning
confidence: 85%
“…14 Regarding HBV and HCV, only 4 studies examined the validity of using International Classification of Diseases (ICD), Ninth Revision, Clinical Modification (ICD-9-CM) codes to identify patients with HBV or HCV infection. [15][16][17][18] The data used in 2 studies were confined to one medical center. These studies had small sample sizes (n = 331 and 200, respectively), and only the positive predictive value (PPV) was estimated to evaluate the validity of ICD-9-CM codes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research efforts have found administrative codes to have good utility for communicable disease surveillance when diseases are common and have simple case definitions and clinical diagnoses (Sickbert‐Bennett et al., ). Investigations into using these codes for cryptococcal meningitis and hepatitis B virus infection determined that they were accurate and useful for surveillance of those diseases (Mahajan et al., ; Pyrgos et al., ). However, other researchers have concluded that the use of administrative codes is not a viable alternative to public health surveillance, as the codes had low sensitivity and positive predictive value, were not useful for rare diseases or those with complex case definitions and diagnoses, and were resource‐intensive for surveillance purposes (Fiske, Griffin, Mitchel, Sterling, & Grijalva, ; Mullen et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…International Classification of Diseases, 9th Revision, Clinical Modification (ICD‐9‐CM) codes (also referred to as administrative codes in this paper) are typically used for administrative purposes such as billing. Others have previously explored the use of these codes to support or supplant traditional public health surveillance and to address some of the surveillance issues highlighted above (Elkin & Brown, ; Mahajan, Moorman, Liu, Rupp, & Klevens, ; Pyrgos, Seitz, Steiner, Prevots, & Williamson, ; Sickbert‐Bennett, Weber, Poole, MacDonald, & Maillard, ). Results are mixed and depend on the disease in question.…”
Section: Introductionmentioning
confidence: 99%